The Effect of Lecturer Certification on Improving Teaching Performance: A Case Study of Japanese Language Lecturers in West Java - Setiana, S M; Yukasih, I M; Dirgandini, M; Halibanon, D S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Government of the Republic of Indonesia provides allowances for certified lecturers to improve the quality of lecturers. Lecturer certifications are competency tests for lecturers who have met the professional lecturer certificate requirements. The purpose of this study is to discuss the effect of lecturer certification on improving the teaching performance of lecturers. The method used in this research is the descriptive method. Data was collected by distributing questionnaires online. Respondents in this study were 25 Japanese language lecturers from 7 private universities in West Java namely Universitas Komputer Indonesia, Universitas Kristen Maranatha, Universitas Nasional Pasim, Universitas Widyatama, STBA Yapari Bandung, Universitas Pakuan, and IPB Cirebon who have been lecturer certified. This research was conducted from July to November 2022. The results showed that lecturer certification has a significant positive effect on improving the teaching performance of lecturers. This can be seen from the high influence of lecturer certification on increasing the pedagogical, professional, social and personal competence of lecturers, thus increasing the quality of Japanese language learning. It is hoped that this can also improve students' abilities in hard skills and soft skills to face competition in the global market. Therefore, continuous self-quality improvement for certified lecturers is needed.